A Comparative Study on the Anti-Diabetic Potential of Aloe vera Gel and Fenugreek Seeds on Experimentally induced Diabetic Rats - Vanitha, M; Karpagam, T; Varalakshmi, B; Pandian, R. Suja (Pharmacognosy Communications)
In the present study, the anti-diabetic property of an ethanolic extract of Aloe vera leaf gel and fine crude powder of Fenugreek seeds were compared. Oral administration of Aloe vera gel extract at a concentration of 300 mg/kg body weight and Fenugreek seeds powder extract at a concentration of 2g/kg body weight to alloxan-induced diabetes in rats significantly decreased the levels of blood glucose and glycosylated hemoglobin. The increased levels of lipid peroxidation in the pancreas of diabetic rats were reverted back to near normal levels after the treatment with Aloe vera gel and Fenugreek seeds powder extract. A significant increase was observed in SOD, vitamin C, vitamin E levels in Aloe vera gel and Fenugreek seeds powder extract treated rats. These extracts were also more effective than glibenclamide in restoring the levels to near normal.
Keywords: Aloe vera; Fenugreek seeds; Alloxan-induced diabetes; anti-diabetic